The evolution of the Rapidrive Driving School Instagram metric - Andraus Quintero, Cesar (2025)
Social media have become fundamental in communication and marketing. Instagram, one of the leading platforms, offers opportunities for audience interaction and engagement. This study analyzes the evolution of the Instagram metrics of the Rapiddrive Driving School in the period from October 2022 to May 2023. Variables such as reach, interactions, and follower growth were evaluated through quantitative analysis. The results highlight the importance of quality, authentic content in attracting followers and maintaining engagement. The variability in the metrics was analyzed using measures of central tendency and dispersion, revealing significant patterns. Follower growth and engagement rates have fluctuated, influenced by temporary events and specific content. Content strategy on Instagram, including posts, reels, stories, and videos, plays an essential role in reaching and engaging. Continuous adaptation and active community management are crucial for sustainable growth. The results offer a foundation for future digital marketing decisions, taking advantage of changing audience preferences and opportunities in the digital environment.